METODE CAMEL UNTUK MENILAI TINGKAT KESEHATAN PD. BPR. ROKAN HULU PASIR PENGARAIAN - Afriyanto (Jurnal Ilmiah Cano Ekonomos, 2015)
The health of banks is a condition assessment of the bank's financial statements at agiven time period and in accordance with Standard Bank Indonesia assessed with aqualitative approach on various aspects affecting the condition and development of a bank.Implementation of the assessment carried out by qualified some of the components of eachfactor is a component of Capital, Asset, Management, earnings (profitability), Liquidity orabbreviated terms CAMEL. The research was conducted in PD. BPR Rokan Hulusubdistrict Sand Pengaraian Rambah. To collect the study data, researchers used datacollection techniques in the form of documentation by asking some of the documentssupporting the company or related to this research. In analyzing the data obtained, theresearcher uses descriptive method that the data obtained is then arranged so that it can beanalyzed properly and accurately based on the theory that are relevant to the issues to beconcluded later. Based on the research that has been done can be seen that the level of thefinancial health of PD. BPR Rokan Hulu Sand Pengaraian are in a healthy condition forcapital aspect, the aspect of assets (ratio KAP), management aspects, aspects of earnings,and liquidity (LDR). While the level of the financial health of PD. BPR Rokan Hulu SandPengaraian are in unsanitary conditions for aspects of assets (PPAP ratio) and liquidity(cash ratio).